Synergism of Plant Compound With Traditional Antimicrobials Against Streptococcus spp. Isolated From Bovine Mastitis - Maia, Natasha L.; de Barros, Mariana; de Oliveira, Leandro L.; Cardoso, Silvia A.; dos Santos, Marcelo H.; Pieri, Fabio A.; Ramalho, Teodorico C.; da Cunha, Elaine F. F.; Moreira, Maria A. S. (Frontiers in Microbiology, 2018)
Mastitis is an inflammation of the mammary gland that causes major losses in the dairy industry. Streptococcus spp. are among the main agents of this disease. Increased resistance to antibiotics is one of the causes of therapeutic failure. Plants, due to their broad chemodiversity, are an interesting source of new molecules with antibacterial activity. Using these compounds along with traditional antibiotics is a possible method for reversing resistance. The objective of this work was to determine the interactions between the activities of guttiferone-A and 7-epiclusianone, two active substances isolated from the fruits of Garcinia brasiliensis, and traditional antibiotics against Streptococcus spp. isolated from bovine mastitis and known to be resistant to them. First, the MIC for the antibiotics and bioactive compounds was determined, followed by their activities, alone and in combination. Then, their cytotoxicity was measured in bovine mammary epithelial cells. Finally, molecular docking simulations were performed to elucidate molecular details of the interactions between β-lactamase and the compounds binding to it (clavulanic acid, ampicilin, 7-epiclusianone and guttiferone-A). The bacterial isolates were resistant to ampicillin and gentamicin. Both antibiotics showed predominantly synergistic antibacterial activities in combination with guttiferone-A or 7-epiclusianone. These two active substances were not cytotoxic at synergistic concentrations and both showed strong binding to β-lactamase, which may explain the reversal of ampicillin resistance. These substances are promising for the treatment of bovine mastitis.